Male chicks play more than females – sex differences in chicken play ontogeny - Oscarsson, Rebecca; Jensen, Per (Frontiers in Ethology, 2024)
Play indicates positive affective states and can therefore potentially be used as an indicator of positive welfare. Sex differences in play has been reported in many mammalian species, but in birds, this is still to be explored. It is known that young chickens perform play behavior during their early ontogeny, but potential sex differences have not previously been addressed. Therefore, we aimed to investigate potential sex effects on play ontogeny in young chickens, by comparing play occurrence in young males and females of a commercial hybrid of White Leghorn. Eighteen chicks of each sex were hatched in the same incubator and then housed in sex-separated groups. Six groups of three chicks each were randomly created for each sex, and the same three chicks were then moved to enriched play arenas twice per week, from day 6 until day 53 post hatch. The frequency of different play behaviors, categorized as locomotor play, social play and object play were recorded during 30 min on each observation day. Each group of three birds constituted the independent statistical replicate. Males played significantly more than females, due to more social and object play, whereas for locomotor play, no difference was found between the sexes. In conclusion, clear sex differences in play in chickens was demonstrated, and this may be linked to the highly sexually dimorphic behavior of adult cockerels and hens. Further research is needed to elucidate the relationships between type and frequency of play in chicks and later behavior as adults.